Bottlenecks and opportunities for improvement in cybercrime handling: insights from Dutch police practice - Leukfeldt, E. R. (Deviant behavior, 2025)
This study examines the handling of cybercrime cases by law enforcement officers, focusing on bottlenecks and potential improvements noted by experts in the field. Building on previous research, this study identifies persistent issues such as low prioritization, a lack of capacity, knowledge gaps, and case complexity. Respondents advocate for the centralized processing of online crime reports to enhance data aggregation, improve detection of overarching patterns, and streamline investigative efforts. The study underscores the ongoing struggle to adapt law enforcement practices to the ever-evolving landscape of cyber threats, emphasizing the necessity for comprehensive reform to optimize response strategies.